Niche-mediated bacterial community composition in continental glacier alluvial valleys under cold and arid environments - Chen, Xianke; Qi, Xiangning; Ren, Ge; Chang, Ruiying; Qin, Xiang; Liu, Guohua; Zhuang, Guoqiang; Ma, Anzhou (Frontiers in Microbiology, 2023)
Bacteria are an essential component of glacier-fed ecosystems, and play a dominant role in driving elemental cycling in hydrosphere and pedosphere. However, studies of bacterial community composition mechanisms and their potential ecological functions from the alluvial valley of mountain glaciers are extremely scarce under the cold and arid environments. Here, we analyzed the effects of major physicochemical parameters related to soil on the bacterial community compositions in an alluvial valley of the Laohugou Glacier No. 12 glacial meltwaters from perspective of core, other, and unique microbiome, and explored their functional composition characteristics. The different characteristics of core, other, and unique taxa highlighted the conservation and difference of bacterial community composition. Bacterial community structure of glacial alluvial valley was mainly affected by the above sea level, soil organic carbon, and water holding capacity. Besides, the most common and active carbon metabolic pathways and their spatial distribution patterns along the glacial alluvial valley were revealed by FAPTOTAX. Collectively, this study provides new insights into the comprehensive assessment of glacier-fed ecosystems in glacial meltwaters ceasing or glaciers disappearance.